PENGARUH INFLASI, INDONESIAN GOVERMENT BOND/SUN YIELD, KURS DOLLAR, PERTUMBUHAN GDP TERHADAP INDEKS LQ45: DENGAN INDEKS IHSG SEBAGAI VARIABEL INTERVENING DI BURSA EFEK INDONESIA (Study empiris di Bursa Efek Indonesia tahun 2011 – 2016) - Riko Sutriyadi (POLITEKNIK LP3I JAKARTA, 2019)
This study aims to analyze the effect of inflation, Indonesian government bond / SUN yield, dollar exchange rate, GDP growth on the LQ45 index, with the IHSG index as an intervening variable on the Indonesia Stock Exchange (Empirical Study on the Indonesia Stock Exchange in 2011-2016). This study uses purposive sampling with weekly data (week to week) for 5 years starting from January 2011 to January 2016 and obtained a population of 263 weeks. The statistical method used in this study is inferential statistics that is multiple linear regression analysis with time series data that is processed using Eviews 7 software. The results showed that partially the inflation variable had a negative and significant effect on the LQ45 index, The Indonesian Government Bond / SUN yield had a positive and significant effect on the LQ45 index, the dollar exchange rate had a positive and significant effect on the LQ45 index, GDP growth had a positive and significant effect on the index LQ45. Inflation variable has a negative and significant effect on the JCI index, The Indonesian Government Bond / SUN yield has a positive and significant effect on the JCI index, the dollar exchange rate has a positive and significant effect on the JCI index, GDP growth has a positive and significant effect on the JCI index, LQ45 Index has a positive effect and significant on the JCI index and simultaneously intervening variables, namely inflation, The Indonesian Government Bond / SUN yield, dollar exchange rate, GDP growth and LQ45 index have a significant effect on the index index JCI. The conclusion from the results of this study is that there is no significant effect on the research gap proposed by the author.Keywords: inflation, SUN yield, GDP, LQ45 index, IHSG index.